In Silico Study of Cembranoid-Type Diterpene Targeting Kirsten Rat Sarcoma Virus (KRAS) Gene in Lung Cancer - Teuku Baihaqi Septiady; Muhammad Rafli Hidayatullah; Ainur Rofiq; Afifah Endah Dwi Purianti; Indyra Mahrani Lubis; Nesya Alya Fayyaza; Humairah Medina Liza Lubis (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Lung cancer is genetic changes in the V-Ki-ras2 gene Kirsten rat sarcoma viral oncogene homolog(KRAS), which is involved in signaling pathways related to proliferation, cell differentiation, andapoptosis. Point mutations in the KRAS gene were detected in 15% to 20% of all Non-Small Cell LungCarcinoma (NSCLCs) and about 30% of lung adenocarcinomas, with the most common mutation beingat codon 12. This study aimed to determine the binding reaction between diterpene-type cembranoidcompounds from tobacco leaves (Nicotiana tabacum L.) and KRAS in human lung cancer. We foundthe presence of a cembranoid-type diterpene active compound in the form of thunbergol (C20H34O)with Gas Chromatography and Mass Spectroscopy (GC-MS) examination. Based on the resultsof molecular docking, it was found that the diterpene-type cembranoid ligand binds to the KRASreceptor with a yield of G -7.0 kcal/mol, pKi 7.35 M, one hydrogen bond with type ILE36 (1,937 Å).In conclusion, diterpene-type cembranoid can be considered an anticancer compound because of themolecular interaction with cembranoid-type diterpene through cell proliferation and differentiationpathways, as well as apoptosis.